Rola mediacji dydaktycznej w rozwijaniu warsztatu poznawczego ucznia na lekcji języka obcego - Sujecka-Zając, Jolanta (Neofilolog, 2017)
Each learning is, by its very nature, a situation of conflict as well as cognitive and socio-affective, and its intensity depends on the learner's existential competence (savoir-être) and individual differences. To learn effectively, one must regularly use cognitive tools that constitute the mental equipment of the person. The teacher as a mediator could encourage the learner to better use the tools he or she already has or to develop new tools that are missing for now. The theoretical remarks will be supported by examples from empirical research in which Didactic Dialogue has been used, which is an approach for didactic mediation in the language class.